Organoleptic, physicochemical, phytochemical and pharmacological evaluation of six medicated ghee used for Ayurvedic management of Epilepsy - Snehal Moon; Nishikant Raut; Harshal Moon; Anmol Dhawande; Shailendra Gurav (Journal of Ayurveda and Integrative Medicine, 2024)
Background: Ayurvedic formulations need to be explored and tested with biomedical techniques. Polyherbal medicated ghee (Ghrita) are recommended for the management of epilepsy (Apasmara) and prepared using specialized process (Snehapaka), as per classical textbooks of Ayurveda. So, the present study deals with the systematic examination of the effect of different marketed formulations for treating Apasmara on convulsive impairment in Pentylenetetrazol (PTZ) induced seizures in mice. Objective: To assess organoleptic, physicochemical, phytochemical and pharmacological activity of selected Ghrita formulations used to treat Apasmara. Materials and Method: Six marketed Ghrita formulations used for Apasmara, such as Baidyanath Brahmi Ghrita (BBG), Patanjali Brahmi Ghrita, Kotakkal Brahmi Ghrita, Panchagavya Ghrita, Mahapanchagavya Ghrita and Nirgundyadi Ghrita were selected for the study. Selected Ghrita formulations were subjected to physicochemical analysis (following pharmacopeial procedures), phytochemical screening and pharmacological profile for quality and therapeutic efficacy. The screening parameters included pH, viscosity, specific gravity, loss on drying, acid value, saponification value, peroxide value, iodine value, refractive index and rancidity determination, and other phytochemical tests for secondary metabolites. Results: BBG demonstrates superior protection against the onset and duration of convulsions compared to alternative Ghrita formulations. As evidenced by its efficacy in mitigating PTZ-induced convulsions, BBG stands out as the optimal choice for exerting potent anticonvulsant effects. Conclusion: In-vivo screening suggests BBG as a potential Ghrita preparation for treatment of epilepsy.